Peningkatan Keterampilan Menulis Bahasa Arab (Kitābah) dengan Menggunakan Metode Scramble di Program Studi Pendidikan Bahasa Arab, Universitas Negeri Jakarta - Hendrawanto Ch (Al-Ma‘rifah, 2020)
The main purpose of this study is to find a clear description of the effectiveness of using the scramble method to improve students’ proficiency in Arabic writing skills. This research is a qualitative study using a class action research method for 4th-semester students of 2016, in the Arabic language Education Study Program, Faculty of Languages and Arts, Universitas Negeri Jakarta, who took Kitābah 1 course. The results of this study indicate that there are changes in the attitudes and behavior of students who study Kitābah 1 with the scramble method before and after applying the method, starting from the pre-research to the first and second cycles. In this second cycle, there is a very significant change compared to before where students are more active in asking questions and discussing with their groups. Because of their activeness, the results obtained were also significant changes. This is proven by the following changes: there are 29 out of 85 students who get “very good” grades, 37 students get “good” grades, and 15 students who have “enough” grades. Meanwhile, only 4 students scored “less”. The lack of value is because the student concerned did not enter the lecture so the value and understanding are lacking in the material that has been submitted.